Legal Certainty Reconstruction of Dropshipping Transactions in The Batam Free Trade Zone from The Perspective of The Rule of Law - Totok Catur Wismo Malaicanto; Binsar Jon Vic (Indonesian Journal Publisher, 2026)
The development of the digital economy has driven the emergence of new business models in electronic commerce, one of which is the practice of dropshipping. This business model allows business actors to conduct sales transactions without physically owning or storing goods. Although it provides significant economic opportunities, dropshipping also raises various legal issues, particularly regarding legal certainty in trade and taxation systems. This study aims to analyze the legal certainty of dropshipping transactions in the Batam free trade zone and to formulate a legal reconstruction model capable of providing legal certainty for business actors. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The theoretical framework of this research utilizes the Rule of Law concept as articulated by Tom Bingham. The results indicate that dropshipping practice in the Batam free trade zone still faces several legal issues, including the absence of specific regulations governing dropshipping, inconsistencies between tax regulations and customs policies, and limitations in digital transaction monitoring systems. Therefore, this research offers legal reconstruction through the establishment of specific dropshipping regulations, integration of taxation and customs systems, and the development of tax administration mediation mechanisms as an alternative dispute resolution. This legal reconstruction model is expected to create a more adaptive regulatory system for the digital economy while providing greater legal certainty for business actors in the Batam free trade zone.